2021
DOI: 10.5812/amh.113123
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Endurance Training with Crocin Consumption on the Levels of AMPK and NRF1 Gene Expression in the Soleus Muscles of Diabetic Rats

Abstract: Background: Exercise training and crocin, as a herbal antioxidant, help improve metabolism and insulin sensitivity in type 2 diabetes mellitus (T2D). AMP-activated protein kinase (AMPK) and nuclear respiratory factor 1 (NRF1) involve in the mitochondrial biogenesis pathway and diabetes control. Objective: This study aimed to investigate the effects of high-intensity interval training (HIIT), and low intensity continued training (LICT) in combination with crocin consumption on AMPK and NRF1 gene expression in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Few studies suggested that antioxidants supplementation may be beneficial under specific circumstances, such as overtraining, high-altitude training, or hypoxic training, and claimed that antioxidant usage such as the intake of vitamin E or vitamin C may have no benefit at all or may even cause harm [ 6 , 7 , 29 , 176 , 256 ]. Misusing or consuming excessive amounts of vitamins can lead to muscle fatigue and impede the recovery process due to the inactivation of the gene expression regulator Nrf2 (Nuclear factor erythroid 2-related factor 2), which plays a role in the response to cellular stress and contributes to enhancing exercise performance [ 265 ]. It is worth noting that Vitamin E toxicity may cause increases in mortality risk factors, since there has been a positive relation accompanied by a high-sensitivity C reactive protein indicative of inflammation [ 266 ].…”
Section: Vitamin Ementioning
confidence: 99%
See 2 more Smart Citations
“…Few studies suggested that antioxidants supplementation may be beneficial under specific circumstances, such as overtraining, high-altitude training, or hypoxic training, and claimed that antioxidant usage such as the intake of vitamin E or vitamin C may have no benefit at all or may even cause harm [ 6 , 7 , 29 , 176 , 256 ]. Misusing or consuming excessive amounts of vitamins can lead to muscle fatigue and impede the recovery process due to the inactivation of the gene expression regulator Nrf2 (Nuclear factor erythroid 2-related factor 2), which plays a role in the response to cellular stress and contributes to enhancing exercise performance [ 265 ]. It is worth noting that Vitamin E toxicity may cause increases in mortality risk factors, since there has been a positive relation accompanied by a high-sensitivity C reactive protein indicative of inflammation [ 266 ].…”
Section: Vitamin Ementioning
confidence: 99%
“…Moreover, it is necessary for several other cellular functions, including the development of nucleic acid precursors, myelin, and neurotransmitters (such as acetylcholine), as well as antioxidant defense [ 272 ]. A deficiency of this vitamin leads to a decline in oxidative metabolism [ 265 ]. The biochemical outcomes include a failure to create adenosine triphosphate (ATP), lactic acidosis resulting in a greater lactic acid generation, and a reduction in neurotransmitter synthesis (e.g., acetylcholine, glutamate, aspartate, and gamma-aminobutyric acid (GABA)) [ 6 ].…”
Section: Water-soluble Vitamins (Wsv)mentioning
confidence: 99%
See 1 more Smart Citation